How To Respond to Catastrophic Events in Supply Chain Management - Choi, Sooyeon (2011)
In March of 2011, a massive earthquake and tsunami struck into Japan. Soon after this event, Toyota in the UK announced that their production had to been halted caused by disruption on supply chain relationship with Japan. Like this, a catastrophic event disturbs not only domestic situation but also international business. Supply chain is one of the most affected areas and also capable to control on business at the same time when a disaster occurs. In this work, how to respond supply chain system in different catastrophic events is studied through real cases in past decades and analysis on the different responses of different situation on different company is attempted. By the analysis, it is found the ways to build frameworks for preparedness for catastrophic event in order to make the right decision and respond in the right direction without unnecessary losses but with being resilient, contingent. The framework developed from the literature and the conclusion of past cases included the following aspects-supply management, demand management, product management, information management and supply chain network design. By following this framework, business can be well prepared for unexpected catastrophic events and their effects on the supply chain.